MERANCANG KUIS INTERAKTIF MENGGUNAKAN MACROMEDIA DIRECTOR 8 - Umar Mansyuri (LPPM Universitas Bina Bangsa, 2021)
Today, with the development and advancement of technology that is increasingly sophisticated, it is easier for humans to communicate and get or send the information needed. Vaughan (1998) defines multimedia as a collection of ways that humans use to communicate and get information called media. Media is something that is needed in various aspects or fields of human life, for example in educational institutions, entertainment, health, training, and other fields. One multimedia-based application that can be used as a tool to help in education is interactive quizzes. Where with this interactive quiz application an educator no longer needs to correct the results of the quiz to see the results but automatically after students work on the interactive quiz, the final result is immediately visible on the last sheet of this quiz. In this simple article, the software used in making this interactive quiz is Macromedia Director 8